A consensus approach to improving patient adherence and persistence with topical treatment for actinic keratosis. (10th April 2015) - Stockfleth, Eggert; Peris, Ketty; Guillen, Carlos; Cerio, Rino; Basset‐Seguin, Nicole; Foley, Peter; Sanches, José; Culshaw, Alex; Erntoft, Sandra; Lebwohl, Mark
Abstract: Background: Topical therapy is important in the treatment of actinic keratosis, but guidance for improving adherence/persistence during topical therapy is still lacking. Objectives: To utilize expert consensus to generate a list of recommendations to improve real‐world efficacy when prescribing topical therapy for actinic keratosis. Methods: An expert panel of eight dermatologists was convened to generate recommendations based on facilitated discussion and consensus generation using a modified Delphi session. The recommendations were ratified with the expert panel. Results: Facilitated discussion generated 31 issues within five themes, which were prioritized using expert voting. Consensus was achieved on the importance of short and simple treatment regimens for maximizing patient compliance, physician awareness of the progression of actinic keratosis to squamous cell carcinoma, provision of appropriate patient information, and the use of effective communication strategies to educate physicians about actinic keratosis. Based on these key findings, eight recommendations were generated. Conclusions: The recommendations will assist physicians when prescribing topical actinic keratosis therapy. Further research should focus on the types of patient outcomes that are influenced by the characteristics of topical field therapy.